Optimization of Sintering Parameters and Post Sintering Characterisation in Mullite-Zircon Ceramics - YUMUŞAK, GÖRKEM; ARTIR, RECEP (My University, 2023)
In this study, with the help of the known effect of Fe2O3, which is a sintering aid additive for sintering, it is possible to synthesize products at temperatures much lower than 1500°C, which is the known sintering temperature in the phase diagram of the mullite-zircon system. In addition to the phase and microstructure analysis of the produced products as a result of the addition of sintering aid additive (Fe2O3) and reaction sintering process, mechanical characterizations were performed. The sintering aid additive (Fe2O3) was mixed into the Mullite-Zircon structure by adding 1 wt.%, 2 wt.% and 3 wt.%. 1% by weight of PAN was used as the binder. This mixture was formed into pellets before sintering under the selected pressing force of 2500 psi. These pellets were sintered at 1500°C, 1450°C, and 1400°C sintering temperatures, respectively, with a sintering time of 5 hours for each temperature. As a result of these processes, the effect of sintering temperature and the effect of the amount of sintering aid additives were examined by using characterization methods. It was aimed to determine the optimum parameters for this material, considering the important properties of ceramics such as porosity, hardness, density, and microstructure of the product to be produced with these additives and parameters. X-Ray Diffraction analyses were performed, and the phases formed as a result of the reaction were determined. Microstructure analyses were made for sintering temperatures of 1500°C, 1450°C, and 1400°C using an optical microscope. The optimum sintering temperature for the parameters used in this study and the amount by weight of the sintering aid additive to be used were selected considering variable factors in this study, and it was aimed to find the product with the best properties and the lowest cost.
Keywords: Metalurji ve Malzeme Mühendisliği; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING